Mapping the Halal Industry: A Decade of Bibliometric Trends and Strategic Implications for Islamic Economics Education in Indonesia - Riyadi, Slamet; Rozaanah (RAFAHIYA Jurnal Ekonomi dan Syariah, 2025)
This study maps the global research landscape of the halal industry (2013–2023) through bibliometric analysis, identifying thematic priorities, collaboration gaps, and opportunities for academic institutions offering Islamic economics programs. Using Scopus data analyzed via VOSviewer and Mendeley, 1,156 publications were systematically reviewed. Co-occurrence, overlay, and density visualizations were employed to decode thematic clusters, temporal trends, and research gaps. The analysis reveals three key insights: (1) Dominance of halal food (53 occurrences) and tourism (26) research, overshadowing emerging sectors like halal pharmaceuticals (2); (2) Geographic concentration in Malaysia (15), Indonesia (4), and Turkey (3) with limited cross-border collaboration (82% single-country publications); (3) Critical gaps in sustainability integration, non-Muslim market studies, and technology ethics.Practical implications: For Indonesian universities, these findings highlight the urgency to (a) redesign curricula emphasizing understudied sectors (e.g., halal fintech, ESG compliance), (b) foster international partnerships to overcome regional fragmentation, and (c) bridge doctrinal compliance with SDGs through applied research. This study is the first to systematically link halal industry bibliometrics with Islamic economics education strategies, offering a roadmap for curriculum innovation and global academic leadership.